2016
DOI: 10.1007/s12010-016-1999-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of Butyrate from Lactate by a Newly Isolated Clostridium sp. BPY5

Abstract: Lactate-utilizing bacteria play important roles in the production of Chinese strongflavored liquor (CSFL). However, the identity of these bacteria and their lactate-utilizing properties are largely unknown. Here, a lactate-utilizing, butyrate-producing bacterium BPY5 was isolated from an old fermentation pit for CSFL production. The isolate represented a novel species belonging to Clostridium cluster XIVa of family Lachnospiraceae based on phylogenetic analysis using 16S rRNA gene sequences. Strain BPY5 could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 39 publications
5
28
0
1
Order By: Relevance
“…Lactate has also been described to generate the acetyl-CoA to provide the two carbon atoms for the acetate to n -butyrate elongation via reverse β-oxidation, in which the oxidation of lactate to pyruvate produces NADH and the conversion of pyruvate to acetyl-CoA with ATP generation. However formerly, propionate and butyrate are the major products, and few caproate is produced from lactate [ 4 , 15 ]. Recently, a series of studies showed that lactate (as ED) can be efficiently converted into CA with reactor microbiomes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lactate has also been described to generate the acetyl-CoA to provide the two carbon atoms for the acetate to n -butyrate elongation via reverse β-oxidation, in which the oxidation of lactate to pyruvate produces NADH and the conversion of pyruvate to acetyl-CoA with ATP generation. However formerly, propionate and butyrate are the major products, and few caproate is produced from lactate [ 4 , 15 ]. Recently, a series of studies showed that lactate (as ED) can be efficiently converted into CA with reactor microbiomes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol has been proved to be the efficient reducing substrate for CA synthesis (Agler et al, 2012;Barker and Taha, 1942;Grootscholten et al, 2013). Lactate, as an energy-rich reducing compound, has generally been reported to be used to produce butyrate (Prabhu et al, 2012;Tao et al, 2016;Weimer and Moen, 2013). Only trace amount of CA production (0.26-0.48 g/L) from lactate have been reported for the fermentation with M. elsdenii (Marounek et al, 1989).…”
mentioning
confidence: 99%
“…As for the deployed uncoated pumice slurries, lactate metabolism was observed in the absence of an electron acceptor (Fe(III); Figure 4B), suggesting the presence of other electron acceptors, such as insoluble manganese or sulfate minerals (Sousa et al, 2017;Novotnik et al, 2019), sorbed or precipitated from the spring water. Alternatively, fermentation of lactate could also occur in the absence of an electron acceptor (Oude-Elferink et al, 2001;Tao et al, 2016). This indicates that the source of the sulfate in the deployed Fe(III)-coated pumice slurries is most likely from the spring water well.…”
Section: Geochemical Changes During the Incubation Of The Deployed "Mmentioning
confidence: 99%